Integrating Stability Assessments Under the Financial Sector Assessment Program into Article IV Surveillance-Background Material. (Policy Papers; Policy Paper ;, 2010)
This paper presents the staff analysis underpinning two central elements of the proposal to make financial stability assessments under the FSAP mandatory for members with systemically important financial sectors: the definition of systemic importance used in the paper and the methodology for identifying members with systemically important financial sectors (Section II); and the review of the literature and industry practices that form the basis for the staff proposal to conduct these mandatory financial stability assessments at a frequency of about three years (Section III).